Studying the sensitivity of the computer capillaroscopy method with local changes in temperature - Аврунін, О. Г.; Ковальова, А. А.; Avrunin, O. G.; Kovaleva, A. (ДЗ «НПМ РДЦ МОЗ України», 2020)
Computerized capillaroscopy makes it possible to reveal on the evidence level the peculiarities of the functioning of the peripheral circulation system according to the state of the capillary and to evaluate the effectiveness of treatment according to the aggregation state of blood, the state of blood rheology in hematological practice. This method is especially relevant in the diagnosis of any disease, since it expresses any changes and disorders in the body, including local frostbite.
Keywords: capillaroscopy; circulation; image processing; thermoscope